Meningkatkan Minat Belajar Siswa Menggunakan Aplikasi Multimedia Pembelajaran Mobile - Tri Sugihartono; Rendy Rian Chrisna Putra (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
The rapid development of science and information technology, electronic technology has also developed rapidly. Indirectly, human lifestyle is influenced by the presence of a variety of sophisticated electronic equipment. With the development of technology and computer-based electronic equipment, many people already have such smartphones and tablets. These tools can help facilitate daily activities, for example student learning with an Android-based application. The problem with early childhood is a limited knowledge base, they need an understanding of letters, numbers, types of animals, and fruit names. Learning patterns of children who like to play greatly affect the concentration of children in learning. They are easily bored with theoretical material that is delivered verbally by the teacher and parents, children understand the material in the form of images faster. Therefore, this research discusses the application of multimedia learning to increase student interest in learning that can help in their learning process. the results of this study are the presence of multimedia learning applications, students can more easily understand and can increase interest in learning, feel interested and challenged with the exercise features in the form of multimedia.